PERENCANAAN KAPASITAS PERCETAKAN ETHICA GROUP MENGGUNAKAN METODE ROUGH CUT CAPACITY PLANNING - Nasywa Hanifa Mutmainah (Jurusan Teknik Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
PT Ethica Megah Madani is a large-scale Muslim clothing manufacturing company. Even the production reaches 1.224.600 pcs per year. Meanwhile, the product produced are Muslim clothes for adults and children, men and women, headscarves, socks, with various different market segments. While the packaging for these products still uses vendors, the company wants a new business unit in the form of packaging printing for its product needs. In starting a new business unit, of course, planning become a reference when the business or production is already running. This study aims to plan the packaging production capacity so that the needs are met. Production capacity is the maximum number of units that can be produced in a certain period of time using available resources. The method used is Rough Cut Capacity Planning (RCCP), which is a method for calculating general capacity requirements and comparing them with available capacity. Next, perform an analysis on machines that lack capacity by adding time. From the processing results, it is known that there is one machine that lacks capacity and needs to be added, namely the screen printing machine